2019
DOI: 10.1002/macp.201800423
|View full text |Cite
|
Sign up to set email alerts
|

Mannobiose‐Grafting Shifts PEI Charge and Biphasic Dependence on pH

Abstract: How the 4% grafting of mannobiose alters the properties of the polyelectrolyte, linear polyethylenimine (PEI), which has protonable amines and is used widely for complexing DNA, is investigated. The pH‐dependence of the PEI charge, zeta potential, and hydrodynamic radius changes when the polymer charge increases beyond 50–60%. According to MD simulations, this transition in pH‐ or charge‐ dependence is a short‐range structural response to amine protonation (i.e., change in intrinsic persistence length) rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 73 publications
(139 reference statements)
4
13
1
Order By: Relevance
“…Thus, the increased stiffness in this regime is likely related to the N–C–C–N torsional angle increasingly being in the trans configuration. Basu et al recently determined the persistence length of PEI at several protonation states using atomistic molecular dynamics simulations . Their results roughly agree with the data shown in Figure b, as they found that L p ≈ 5 Å for uncharged PEI and increases to ∼40 Å for fully charged chains, with the majority of this increase occurring when the chain was highly charged.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…Thus, the increased stiffness in this regime is likely related to the N–C–C–N torsional angle increasingly being in the trans configuration. Basu et al recently determined the persistence length of PEI at several protonation states using atomistic molecular dynamics simulations . Their results roughly agree with the data shown in Figure b, as they found that L p ≈ 5 Å for uncharged PEI and increases to ∼40 Å for fully charged chains, with the majority of this increase occurring when the chain was highly charged.…”
Section: Resultssupporting
confidence: 70%
“…The transition from a weakly charged polyelectrolyte to a highly charged one occurred at the same protonation level in different salt conditions since the average charge–charge distance (shown in Figure a for the zero-salt condition) remained the same at different salt concentrations. R g for various values of α has also been recently calculated using molecular dynamics simulations by Basu et al for 20 mer PEI chains in 50 and 150 mM salt solutions . Despite differences in the chain lengths and force field parameters, the change in R g as a function of α for PEI chains at relatively high salt (150 mM in Basu et al, 150 and 500 mM in this study) has many consistent features in the two simulation studies.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The increasing interest in the atomistic MD simulation of l-PEI-based systems led to the development of a new CHARMM-based atomistic force field for describing l-PEI at four different protonation fractions (0, 1/4, 1/3, and 1/2). In recent MD studies, , the effect of ionic strength (salt concentration) on the structure of l-PEI with 20 and 40 repeat units was examined. Lastly, a recent fully atomistic MD study addressed a very long hyperbranched PEI macromolecule (equivalent to 25 kDa) for which several structural properties were computed, such as the radius of gyration and the three eigenvalues of the average radius-of-gyration tensor under high-, neutral-, and low-pH conditions.…”
Section: Introductionmentioning
confidence: 99%